2011
DOI: 10.1002/jbm.a.33291
|View full text |Cite
|
Sign up to set email alerts
|

The effects of electrospun TSF nanofiber diameter and alignment on neuronal differentiation of human embryonic stem cells

Abstract: Although transplantation of human embryonic stem cells (hESCs)-derived neural precursors (NPs) has been demonstrated with some success for nervous repair in small animal model, control of the survival, and directional differentiation of these cells is still challenging. Meanwhile, the notion that using suitable scaffolding materials to control the growth and differentiation of grafted hESC-derived NPs raises the hope for better clinical nervous repair. In this study, we cultured hESC-derived NPs on Tussah silk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 68 publications
6
77
0
Order By: Relevance
“…As dictated in previous studies on neural and vascular cells (Daud et al 2012;Wang et al 2012;Christopherson et al 2009), fibre diameter does affect the viability of cells. Similarly to our results Christopherson et al (2009) and Daud et al (2012) found that when fibre diameter is around 1-1.5 µm cells have a lower proliferative capacity.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…As dictated in previous studies on neural and vascular cells (Daud et al 2012;Wang et al 2012;Christopherson et al 2009), fibre diameter does affect the viability of cells. Similarly to our results Christopherson et al (2009) and Daud et al (2012) found that when fibre diameter is around 1-1.5 µm cells have a lower proliferative capacity.…”
Section: Discussionmentioning
confidence: 66%
“…These experiments using electrospun scaffolds did not consider the mechanical or physical properties of the scaffolds and the effect this has on the cells. It is well documented that changes is fibre diameter and orientation induce a response of the cells in many tissue types (Yan et al 2012;Balguid et al 2009;Wang et al 2012), but the effect on renal cells has been ignored until now. The diameter of the fibre determines the pore size of the scaffold, and this determines how well cells will penetrate into a scaffold (Balguid et al 2009;Baker et al 2008;Ju et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore a successful differentiation of HMSCs into osteoblastic lineage and subsequent mineralization were observed on PCL nanofibers [76]. Wang et al cultured human embryonic stem cells on fibers made up of Tussah silk fibroin and having diameters of 400 and 800 nm and showed increased cellular viability on the 400 nm fibers [77]. In a study conducted by Yang et al, the rate of neural stem cells differentiation was shown higher on PLLA nanofibers than on microfibers [78].…”
Section: Electrospinningmentioning
confidence: 99%
“…43,44 The proliferation and activity of the cells on the scaffold reduced with the increase of fiber diameter. 45 In this study, we found that ASCs and NSCs could proliferate on the scaffold well, which indicated that cells could survive on this scaffold (fiber diameter, 7.93±1.41 μm). The fibers with diameters between 400-500 nm were easier to adhere; however, the 3D space was not enough.…”
mentioning
confidence: 57%